The Influence of Electronic Word of Mouth (eWOM) in Enhancing the Program Registration Applicants of a Youth Organization - Safitri, Susiana Nur; Sultan, Sultan (Asia Pacific Journal of Management and Education (APJME), 2024)
The study explores the impact of electronic word-of-mouth (e-WOM) on the decision- making process of registering for the AIESEC 2021 program. Conducted using a quantitative survey method, the research applies marketing communication theory to understand the influence of e-WOM on consumer behavior. Surveying 75 registrants from the UPN "Veteran" Yogyakarta class of 2021, the findings reveal a significant and robust positive correlation (0.797) between e-WOM and registration decisions, as confirmed by the Product Moment Correlation Test. Additionally, the statistical significance of this relationship is supported by the t Test (p < 0.05), with the F Test indicating that e- WOM contributes significantly to decision- making, accounting for 62.9% of the variance. However, 37.1% of decision- making factors remain unexplored. These results highlight the pivotal role of e-WOM in shaping consumer decisions, particularly in the context of registering for programs such as JOIN AIESEC 2021. Understanding and leveraging e-WOM can thus be crucial for organizations seeking to enhance their marketing strategies and attract participants to their programs.